2017
DOI: 10.4038/slja.v26i1.8269
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between supraclavicular and infraclavicular approaches for subclavian venous catheterization in adults

Abstract: Introduction:The subclavian vein access has been the standard recommended approach for central venous catheterization both for short and long-term use. Aim is to compare the supraclavicular and infraclavicular approaches for subclavian venous cannulation in regard to success, attempts required, time taken and complications. Material and Methods: All patients satisfying the inclusion criteria were placed either in group supraclavicular (S) or group infraclavicular (I) approach for right subclavian vein and 7FrG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…But overall success rate in group SC was 93.33% whereas, 90% in group IC which is not statistically significant. This was comparable with S Govindswamy et al 17 study. The failure rate in that study were only due to inability to locate vein.…”
Section: Discussionsupporting
confidence: 91%
“…But overall success rate in group SC was 93.33% whereas, 90% in group IC which is not statistically significant. This was comparable with S Govindswamy et al 17 study. The failure rate in that study were only due to inability to locate vein.…”
Section: Discussionsupporting
confidence: 91%
“…[ 5 ] Finally, 17 studies (2568 cases to 2482 cases) from 23 reports were included in this review [ Table 1 ] (NCT04637347). [ 3 , 5 - 7 , 20 - 31 ]…”
Section: Resultsmentioning
confidence: 99%
“…In our meta-analysis, data from 17 trials comprising 2482 participants in whom the failure proportion was measured were pooled [ Table 2 , Figures 2 and 3a ] (NCT04637347). [ 3 , 5 - 7 , 20 - 31 ] The comprehensive results revealed that the SC approach likely reduced the failure proportion compared with the IC approach (RR, 0.63; 95% CI, 0.47–0.86; I 2 = 5%; moderate quality) [ Table 2 , Figure 3a ]. In addition, eight trials that met our definition of failure proportion were subjected to sensitivity analysis ( ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations